Electrostatics of a Tetra-Stranded Polymer: Ionic Condensation and Nonlinear Screening - Barack Ndenga (Publisher, 2025)
The principal physical limitation of a canonical tetra-stranded genome is electrostatics. Bringing four negatively charged polymer backbones into close proximity imposes a severe energetic penalty that cannot be addressed by local bonding alone. In this work, I develop an electrostatic framework for Q-DNA, extending classical Poisson–Boltzmann descriptions and ion-correlation theories to a four-strand geometry. I analyze how multivalent cations, polyamines, and molecular crowding reshape the electrostatic free-energy landscape and can induce effective attraction between strands. I predict distinct ionic signatures and identify environmental regimes in which tetra-stranded architectures become electrostatically favorable relative to duplex DNA. This analysis establishes electrostatics as the dominant gatekeeper for the existence of canonical four-stranded genomes. Keywords: Q-DNA, electrostatics, Poisson–Boltzmann theory, ion condensation, multivalent cations, molecular crowding
This work develops a dedicated electrostatic framework for a canonical tetra-stranded hereditary polymer (Q-DNA), addressing the principal physical limitation of four-strand genome architectures: electrostatic repulsion between multiple negatively charged backbones. Extending nonlinear Poisson–Boltzmann theory and ion-correlation models to tetra-stranded geometries, the manuscript analyzes how electrostatic interactions scale beyond duplex DNA and identifies regimes where mean-field screening breaks down. The study highlights the central role of multivalent cations, polyamines, solvent dielectric properties, and molecular crowding in stabilizing tetra-stranded assemblies through counterion condensation, correlation-induced attraction, and effective ion bridging. It predicts distinct ionic fingerprints for tetra-stranded states and defines electrostatic stability windows in which four-strand architectures become energetically favorable relative to duplex DNA. By formalizing electrostatics as a gating constraint on tetra-stranded heredity, this contribution provides quantitative and testable criteria for evaluating Q-DNA feasibility in synthetic genetics, controlled in-vitro systems, and alternative biochemical environments relevant to origins-of-life and astrobiology research. Resource type: theoretical manuscript / electrostatic model Intended audience: molecular biophysics, theoretical biology, synthetic genetics, and polyelectrolyte physics communities